Meningkatkan Standar Keselamatan: Kajian Implementasi Program K3 Di Hotel X - Habsi Azahra Nur Azizah; Muhammad Naufal Rafi Faras (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
Offices or companies are places often traversed by workers in completing tasks related to the company to achieve its goals. Therefore, offices are places that have potential hazards which certainly affect the safety and health of workers in the office. Data from Badan Penyelenggara Jaminan Sosial (BPJS) Ketenagakerjaan shows an increase in the number of work-related accidents in Indonesia from 2018 to 2020. In 2018, there were 147,000 cases recorded, followed by 114,235 cases in 2019. In 2020, the number of work-related accidents increased to 177,161 cases. This study aims to assess the implementation of occupational health and safety (K3) programs at Hotel X located in Bandung. Data was obtained through observations and interviews, discussing K3 training, incident handling procedures, and K3 program evaluation at the hotel. The results show the existence of comprehensive Standard Operating Procedures (SOP) and training for employees, management involvement in K3 policy development, and routine evaluations to ensure good occupational safety and health.